Wirkmedienbasierte Umformung tiefgezogener Vorformen unter besonderer Berücksichtigung maßgeschneiderter Halbzeuge - Lamprecht, Klaus (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)
Within the scope of this work, a process sequence consisting of deep drawing and a subsequent hydroforming operation has been developed. The use of a rigid drawing punch enables a controlled material flow and thus a purposeful preforming of tailor-made semi-finished products. By means of a following forming stage with an active pressure medium the residual formability of local component areas can finally be used to produce complex secondary shape elements. Based on sheet metal components with an increasing complexity, it is shown that the application of this process sequence allows to open up synergetic effects form both process stages for the extension of the forming limits of tailored product